The Future of Synbiotics: Rational Formulation and Design - Gomez Quintero, David F.; Kok, Car Reen; Hutkins, Robert (Frontiers in Microbiology, 2022)
Synbiotics, mixtures of live microbes and substrates selectively utilized by host organisms, are of considerable interest due to their ability to improve gastrointestinal health. However, formulating synbiotics remains challenging, due in part, to the absence of rational strategies to assess these products for synbiotic activities prior to clinical trials. Currently, synbiotics are formulated as either complementary or synergistic. Complementary synbiotics are made by combining probiotics and prebiotics, with each component acting independently and with the combination shown to provide a clinical health benefit. Most commercial synbiotics as well as those used in clinical trials have been of the complementary type. In contrast, synergistic synbiotics require that the added microbe is specifically stimulated or it’s persistence or activity are enhanced by the cognate substrate. Although several innovative examples have been described in the past few years based on this principle, in practice, relatively few synbiotic studies have tested for synergism. In this review, selected recent examples of complementary and synergistic synbiotics and the rationale for their formulation will be described. In addition, pre-clinical experimental approaches for identifying combinations that provide a basis for satisfying the requirements for synergism will be discussed